Na3Ce(PO4)2:Tb3+ and Na(Mg2–xMnX)LiSi4O10F2:Mn phosphors: a suitable selection for enhancing color quality and luminous flux of remote white light-emitting diodes - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This study proposed the TRP, a remote phosphor structure that has 3 phosphor layers, to ehance the chromatic quality and lumen output for white light-emitting diodes devices (WLEDs). The arrangment of phosphor layers is yellow YAG:Ce3+ phosphor, green Na3Ce(PO4)2:Tb3+ phosphor, and red Na(Mg2–xMnX)LiSi4O10F2:Mn phosphor from bottom to top. Red Na(Mg2–xMnX)LiSi4O10F2:Mn phosphor is used for the red light component to boost color rendering index (CRI). The green layer Na3Ce(PO4)2:Tb3+ phosphor is utilized for the green light component to produce higher luminous flux (LF). With the addition of red and green phosphor, the yellow YAG:Ce3+ concentration must decrease to maintain the 6000 K color temperature. The research results show that red phosphor Na(Mg2–xMnX)LiSi4O10F2:Mn concentration is beneficial for CRI, while green phosphor Na3Ce(PO4)2:Tb3+ is detrimental to CRI. Morever, CQS reaction with red and green phosphor is also studied, which show notable improvement when Na(Mg2–xMnX)LiSi4O10F2:Mn concentration is from 10%-14%, regardless of Na3Ce(PO4)2:Tb3+. The luminous flux (LF) can also increase for more than 40% with the reduced light loss and added green phosphor. Research results are valuable references for producers to enhance the color quality and the light emission of WLEDs.